The Relationship Between Product Quality Management And Customer Satisfaction Control At CV Wery Group, Gunungsitoli City - Zebua, Augusmina; Zai, Kurniawan Sarototonafo; Gea, Jeliswan Berkat Iman Jaya; Gulo, Heniwati (Journal of Management, Economic, and Accounting, 2025)
This research aims to identify and analyze the relationship between product quality management and customer satisfaction control at CV Wery Group in Gunungsitoli City. The background of this study stems from the importance of product quality in maintaining customer loyalty and the company’s competitiveness, especially in a local market characterized by geographical and operational challenges. The research method used is a quantitative approach with a survey technique. Data were collected through the distribution of Likert-scale questionnaires to 83 respondents, consisting of employees and managers of the company. The data were analyzed using validity and reliability tests, Pearson correlation, simple linear regression, coefficient of determination, and t-test to determine the strength and significance of the relationship between the variables.The results of the study indicate a significant and positive relationship between product quality management and customer satisfaction control. This is evidenced by the Pearson correlation coefficient, which falls under the strong category, and a t-test significance value of < 0.05, indicating that the alternative hypothesis is accepted. The coefficient of determination (R²) shows that a large portion of the variation in customer satisfaction control can be explained by the product quality management implemented by the company. In other words, the better the product quality management applied by CV Wery Group, the greater its ability to control and enhance customer satisfaction.